Trafegando por mares, rios, dunas e folhas secas: o entrelugar das transmasculinidades no nordeste brasileiro - Santos, Benjamin Vanderlei dos (Universidade Federal do Rio Grande do Norte, 2024)
Guided by the general objective of discussing the possibilities of masculinities that permeate the experiences of trans men and transmasculine people in the Brazilian Northeast, the research presented here is an ethnocartography produced from the life story narratives of the researcher: a trans man, psychologist and from the Northeast, with other trans men and transmasculine people from the Brazilian Northeast. To this end, meetings were held in the states of Maranhão, Pernambuco and Piauí, where field diary records and semi-structured interviews were used as methodological tools, which were recorded and later transcribed. The fieldwork also includes ethnocartographic experiences carried out in Alagoas and Rio Grande do Norte, through the author's activism in the organized social movement of trans people. Based on decolonial, transfeminist and post-structuralist theoretical frameworks, I present: 1) a state of the art of studies on transmasculinities, resulting from a literature review; 2) gender relations and coloniality situated in the health system and their impacts on access to public policies by trans men and transmasculine people; and 3) a debate on how the constructions of masculinities of trans men and transmasculine people are permeated by signs of a northeastern imaginary that correlates with the meanings produced by hegemonic masculinity while deconstructing them, forming a complex network of expressions of masculinities. This complexity is presented as part of the mobility of power relations that are inscribed in the various ways of being/becoming man, and man is understood here as a relational construction of masculinities based on the different social markers that cross it and that, for this reason, situate transmasculinities in an inbetween place.
Keywords: Transmasculinidades; Narrativa; Nordeste; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA